Comparative analysis of spatio-temporal dynamics in agroforestry systems in African peri-forestrial zones: the case of Guinea and Cameroon - (:unkn) unknown (My University, 2009)
In recent decades rural areas in the forest regions of West and Central Africa have been subject to rapid changes in their physical, social and economical environment. In some cases, local exploitation strategies have evolved towards agroforestry-based cropping systems like coffee and cocoa. The spatio-temporal dynamics of these systems are still poorly understood, however. To better understand these dynamics in the rural zones of two countries, in 2008 a comparative analysis was conducted of two situations in West Africa (Guinea) and Central Africa (Cameroon), both of which are located on the peri-forestrial Guineo-Soudanian savanna. A geo-agronomical approach was adopted, combining aspects of territorial geography and agronomy of farmers’ practices. In both cases the evolutionary spatio-temporal dynamics of agroforestry systems was described and quantified. The results of this study confirm that over the last 3 decades the spatial footprint of agroforestry systems has heavily increased. In particular, coffee-based agroforestry systems have developed at the expense of annual crops in Guinea, while in Cameroon cocoa-based agroforestry systems have spread widely over the savanna. A better understanding of the dynamics of agricultural practices and their impact on peri-forestrial land in Africa is indispensable for a more thorough evaluation of the contribution of agriculture to the evolution of rural areas and their sustainable management. These changes urge a rethinking of analytical tools and intervention evaluations in the face of the challenge of sustainable development
Keywords: African Research